The Role of Parental Concerns in the Recognition of Sepsis in Children: A Literature Review - Harley, Amanda; Latour, Jos M.; Schlapbach, Luregn J. (Frontiers in Pediatrics, 2019)
Background: Sepsis is a time critical disease and outcomes strongly depend on time to initiation of appropriate treatment in hospital. A range of studies have assessed sepsis recognition in hospital settings, whereas little is known about sepsis recognition in the community. The decision-making of parents in seeking medical care may substantially impact survival of children with sepsis. An improved understanding of the parental perspective in recognizing sepsis is urgently needed to inform the design of education campaigns and consideration of using parental concerns as a trigger in sepsis screening tools. Aim: To review the literature on parental concerns in the diagnosis of sepsis in children. Methods: A literature review on parental concerns in pediatric sepsis was performed accessing publications in PubMed, CINAHL and Medline published between 1990 and 2018. In addition, we compared guidelines and online institutional sepsis recognition tools and assessed whether parental concerns were used for screening. Results: Out of 188 articles reviewed, 11 met the criteria. One article was found prospectively assessing the diagnostic performance of parental concern in children evaluated for infection, indicating high positive (16.4) and negative likelihood ratio (0.23) for sepsis/meningitis in presence of parental concerns. The role of parental concern was listed as a sign assisting recognition of sepsis in four studies reporting original data, and six reviews commented on parental concern listed as a factor upon diagnosis of sepsis. When comparing selected examples of institutional sepsis pathways available online, parental concern was variably listed as a criterium to prompt evaluation for sepsis. Conclusions: Despite some guidelines emphasizing the role of parental concern in recognizing sepsis, there is a paucity of data in the field. An improved understanding of whether parental concerns adds diagnostic value to sepsis recognition at acceptable sensitivity and specificity is urgently needed. Future prospective studies should assess whether including parental concerns in sepsis screening tools benefits the assessment resulting in early diagnosis and treatment of children with sepsis.